2015
DOI: 10.1212/cpj.0000000000000128
|View full text |Cite
|
Sign up to set email alerts
|

Dystonia

Abstract: SummaryThere has been considerable progress in our understanding of dystonia over the last century. Growing recognition of dystonia has enhanced awareness of its diverse motor phenomenology and brought attention to the importance that nonmotor features may play in this disorder, once considered to be purely motor. Using the latest technologies in human genetics, new genetic links are being discovered at an ever-quickening pace and expanding our knowledge of the disorder's complex pathogenesis. Furthermore, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 22 publications
2
3
0
1
Order By: Relevance
“…[7][8][9] Throughout childhood (until about 17 years of age), these networks mature by physiologic neurodevelopmental processes, such as selective elimination of neuronal connections and myelination. 13,[37][38][39][40] As implicated by the interconnecting brain networks between the basal ganglia and cerebellum, [10][11][12] we also recognized a striking similarity between the presently reported BFMMS age-relatedness and the previously reported age-relatedness of the Scale for the Assessment and Rating of Ataxia (SARA). 21 Comparing age-relatedness between BFMDRS and SARA scales showed that the BFMMS agerelatedness lingered for a longer time course than that of BFMDS and SARA (≥16 years versus 12 and 10 years 21 of age, respectively).…”
Section: Discussionsupporting
confidence: 83%
“…[7][8][9] Throughout childhood (until about 17 years of age), these networks mature by physiologic neurodevelopmental processes, such as selective elimination of neuronal connections and myelination. 13,[37][38][39][40] As implicated by the interconnecting brain networks between the basal ganglia and cerebellum, [10][11][12] we also recognized a striking similarity between the presently reported BFMMS age-relatedness and the previously reported age-relatedness of the Scale for the Assessment and Rating of Ataxia (SARA). 21 Comparing age-relatedness between BFMDRS and SARA scales showed that the BFMMS agerelatedness lingered for a longer time course than that of BFMDS and SARA (≥16 years versus 12 and 10 years 21 of age, respectively).…”
Section: Discussionsupporting
confidence: 83%
“…Our results are supports the idea of two separate pathophysiology contributing to head oscillations in CD, one originating from the cerebellum and basal ganglia and the other from proprioception. This concept is consistent with the notion that dystonia is a network disorder [28][29][30]. The results also support the idea that although dystonia and tremor often coexist, they may still represent distinct entities with different underlying pathophysiological mechanisms [31].…”
Section: Dystoniasupporting
confidence: 91%
“…According to the network model in CD, the impairment anywhere in the network, even outside of the integrator, may lead to deficits in the feedback dependent neural integration. There is increasing evidence for the involvement of cerebellum, proprioception, and basal ganglia, as three separate sources of the feedback in the network model for CD [28][29][30][31][32][37][38][39]. The cerebellar role in dystonia is supported when the oscillations coexisting with dystonia have sinusoidal features as seen in tremor that is also thought to be related to cerebellar deficits.…”
Section: Dystoniamentioning
confidence: 99%
“…условлен появлением публикаций [4] о наличии высокого уровня тревожно-депрессивных расстройств при данной патологии. G. Heiman и R. Ottman [5] опубликовали данные, доказывающие, что депрессия чаще встречается у носителей мутации дистонии DYT1 при отсутствии клинических проявлений гиперкинеза.…”
unclassified